The smog of exercise: the causal effect of air pollution on fitness behaviors - Cao, Wen; Gao, Tianyu; Ao, Chen; Xiong, Huijun; Li, Na (Frontiers in Public Health, 2025)
With the rapid development of industrialization and urbanization in China, air pollution has become an increasingly serious problem, and people are increasingly concerned about its impact on personal physical and mental health. From the perspective of health behavior, this study investigates the participation of residents in sports activities by examining fitness behavior and using temperature inversion as an instrumental variable for air pollution. Based on the China Family Panel Studies dataset from 2010 to 2018, this paper empirically examines the causal relationship between air pollution and residents’ participation in fitness activities using two-stage least squares. The research results reveal a statistically significant negative correlation: as air pollution intensifies, the likelihood of individuals participating in fitness activities decreases. Additionally, the research results highlight the heterogeneous effects among different demographic groups, including differences in gender, age, education level, household registration, health status, and income status. Overall, this study provides strong evidence for the health-related economic costs of air pollution.